(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores the design and testing of the electrical supply system for automatic control and regulation of the desorber in the gas purification process. The aim of the research was to propose a new approach to improve process efficiency and reduce energy consumption. High-precision sensors, PID controllers, and frequency inverters were used to monitor the operating parameters of the desorber. Test results showed a 15% reduction in power supply fluctuations and a response time shortened to 2 seconds. Additionally, energy consumption decreased by 10% and gas purification efficiency increased by 20%. When compared with other studies, this system demonstrated superior energy efficiency. It is recommended to test the system under industrial conditions and expand integration with IoT technologies.